A primeira pessoa como estratégia de negociação em artigos de opinião - Miskiw, Alice Andrade (2021)
This research is developed from the study of first person in argumentative texts published in Gazeta do Povo newspaper, considering the implications of using this strategy in the construction of the argument. We start from the following research question: What is the discursive-pragmatic role of first person in the negotiation movement in argumentative texts? To answer this question, we set a general purpose: analyze the discursive-pragmatic function of the use of first person in the negotiation movement established in opinion articles produced by columnists, from the perspective of Pragmatics. The analysis undertaken is based mainly on the studies of Pragmatics and uses the research of Parret (1988), Yule (1996), Golder and Coirier (1996), Rodrigues (2001), Fiorin (1996/2007), among others. Methodologically, we propose a qualitative interpretive research (BORTONI-RICARDO, 2008), guided by a descriptive interpretative analysis and by methodological procedures of Qualitative Textual Analysis (MORAES; GALIAZZI, 2011). The data show the recurrence of I and the two types of we (inclusive and exclusive). The recurrence of these forms constituted two categories: Negotiation through the engagement movement and Negotiation through the highlighting of author’s authority. In the first category, in which were selected only inclusive we occurrences, we verified that there is the involvement of an I (writer) with a you (reader) who appears on the text through the use of the first person plural, in a movement that seeks to engage writer and reader. The engagement between the writer and reader seeks to promote an alignment of the reader to the discourse-constructed perspective. In the second category, we verify occurrences of exclusive we and I (first person singular). In this category, the first person is an effective strategy in building the image of a competent enunciator, which also contributes to the reader's adherence to the writer’s perspective. Thus, both the use of inclusive and exclusive we and the first person singular can be understood as an attempt to negotiate in the argumentative text.